Acidic nanoparticles protect against α‐synuclein‐induced neurodegeneration through the restoration of lysosomal function. Issue 4 (23rd March 2022) - Arotcarena, Marie‐Laure; Soria, Federico N.; Cunha, Anthony; Doudnikoff, Evelyne; Prévot, Geoffrey; Daniel, Jonathan; Blanchard‐Desce, Mireille; Barthélémy, Philippe; Bezard, Erwan; Crauste‐Manciet, Sylvie; Dehay, Benjamin
Abstract: Parkinson's disease (PD) is an age‐related neurodegenerative disorder characterized by the loss of dopaminergic neurons in the substantia nigra, associated with the accumulation of misfolded α‐synuclein and lysosomal impairment, two events deemed interconnected. Protein aggregation is linked to defects in degradation systems such as the autophagy‐lysosomal pathway, while lysosomal dysfunction is partly related to compromised acidification. We have recently proven that acidic nanoparticles (aNPs) can re‐acidify lysosomes and ameliorate neurotoxin‐mediated dopaminergic neurodegeneration in mice. However, no lysosome‐targeted approach has yet been tested in synucleinopathy models in vivo. Here, we show that aNPs increase α‐synuclein degradation through enhancing lysosomal activity in vitro. We further demonstrate in vivo that aNPs protect nigral dopaminergic neurons from cell death, ameliorate α‐synuclein pathology, and restore lysosomal function in mice injected with PD patient‐derived Lewy body extracts carrying toxic α‐synuclein aggregates. Our results support lysosomal re‐acidification as a disease‐modifying strategy for the treatment of PD and other age‐related proteinopathies. Abstract : We demonstrated that acidic nanoparticles, after intracerebral injection into a α‐synuclein‐based mouse model of PD, attenuated PD‐related neurodegeneration and synucleinopathy by mechanisms involving a rescue of compromised lysosomes. This study demonstrated that strategies enhancing or restoring lysosomal‐mediated degradation thus appear as tantalizing neuroprotective/disease‐modifying therapeutic strategies and would be of major therapeutic interest for PD.